Research misconduct: A neglected plague - Manjiri A Deshmukh; Arun S Dodamani; Mahesh R Khairnar; Rahul G Naik (Wolters Kluwer Medknow Publications, 2017)
Truthfulness and honesty are absolute essentials of research. But to sustain in the not-so-pleasant "publish-or-perish" environment and "cut-throat" competition to increase the credibility associated with one's name, many individual researchers as well as research groups are turning towards research misconduct and this plague is gradually reaching epidemic and pandemic proportions. This overview highlights the various types and means of research misconduct and gives suggestions aiming to curb this academic menace so that research sanctity and integrity can be preserved and scientific research does not get polluted by the dirt of misreported or fabricated data.